2014
DOI: 10.1002/adma.201400865
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Brushes: Controllable Liquid Transfer in Ratchet Conical Hairs

Abstract: The controllable liquid transfer of a Chinese brush is attributable to the unique anisotropic multi-scale structures of the freshly emergent hairs. A large mass of liquid an be dynamically balanced within the brush as a cooperative effect of the Laplace pressure difference, the asymmetrical retention force, and gravity. Inspired by this, a device is developed with parallel hairs that allows for direct writing of micro-lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
106
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 99 publications
(107 citation statements)
references
References 36 publications
(22 reference statements)
0
106
0
1
Order By: Relevance
“…[14] The controllable liquid transfer was severely impaired when the brush was trimmed, which indicated that the conical tip of the hair played a key role. We recently revealed that the most fundamental of the Chinese brush is the unique anisotropic multiscale structures of the FE-hairs, which feature a tapered architecture with an oriented squama covering (Figure 4a 2 ).…”
Section: Chinese Brush: Controllable Liquid Transfermentioning
confidence: 99%
See 2 more Smart Citations
“…[14] The controllable liquid transfer was severely impaired when the brush was trimmed, which indicated that the conical tip of the hair played a key role. We recently revealed that the most fundamental of the Chinese brush is the unique anisotropic multiscale structures of the FE-hairs, which feature a tapered architecture with an oriented squama covering (Figure 4a 2 ).…”
Section: Chinese Brush: Controllable Liquid Transfermentioning
confidence: 99%
“…Further research indicated that the high adhesive force for water and the large open angle of the pappi play crucial roles in the highly efficient water encapsulation. The former is useful for maintaining the [14] a 1 ) Controllable ink transfer was only achieved on qualified Chinese brushes with conical tips. a 2 ) SEM and AFM images of a single hair.…”
Section: Dandelion Pappi: Efficient Liquid Encapsulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Without the conical fiber ends, Chinese brushes often show droplets at the ends of the brushes after they are removed from ink baths, where these remnant droplets may drop accidentally and leave stains on surfaces. 1 The conical ends of the fibers thus have an important role in controlling liquids within Chinese brushes. Understanding the physical principle behind the hydrostatics of liquids in Chinese brushes may guide the design of liquid-transfer devices.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] In many cases, these devices are dipped in liquid baths and are then removed to keep liquids in the devices, just like Chinese calligraphic brushes, which are traditional writing and painting tools in East Asia. The fibers of Chinese brushes are cylindrical, except for their conical ends.…”
Section: Introductionmentioning
confidence: 99%